Modification Of Sharia In Risk And Return Framework - Azmi Nazri; Afridheani Alifia Lubis; Beautiful Fransiska (Proceeding International Seminar of Islamic Studies, 2019)
This article covers speculations related to risk, consideration of decision making, and also the profit from return in Shariah modification.Types of risks are also discussed in this chapter as for the risks and returns of a single asset both on a single asset (security), a set of assets that make up a portfolio or optimal portfolio.(return) Returns are also divided into two namely Realized Return (Expected Return) and expected return (Expected Return).Selection of Single Assets and Securities Very influential in decision making so that the maximum return is obtained by choosing the optimal portfolio to be the goal of investors in making decisions.